1996
DOI: 10.1074/jbc.271.30.18263
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Protein Phosphatases in the Activation of ICE/CED-3 Protease, Intracellular Acidification, DNA Digestion, and Apoptosis

Abstract: Many events in apoptosis have been identified but their temporal relationships remain obscure. Apoptosis in human ML-1 cells induced by etoposide is characterized by intracellular acidification, enhanced Hoechst 33342 fluorescence, DNA digestion, chromatin condensation, and proteolysis of poly(ADP-ribose) polymerase. This proteolysis is a marker for the action of ICE/CED-3 proteases, which are critical activators of apoptosis. We observed that three serine/threonine protein phosphatase inhibitors, okadaic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 41 publications
12
69
0
1
Order By: Relevance
“…Although the phosphorylation status of Bad in K562 and K562-Tat cells remain to be investigated, it is tempting to speculate that Tat localized in the mitochondria may activate some phosphatases that mediate Bad dephosphorylation, then allowing to form heterodimers with Bcl-X L to exert its apoptotic function (Gajewski and Thompson, 1996;Zha et al, 1996). In this sense, the role of serine phosphatases in the process of apoptosis has been also suggested (Morana et al, 1996). Alternatively, Tat may inhibit the activity of the kinase Raf-1, which has been shown to phosphorylate Bad inhibiting its pro-apoptotic function (Wang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although the phosphorylation status of Bad in K562 and K562-Tat cells remain to be investigated, it is tempting to speculate that Tat localized in the mitochondria may activate some phosphatases that mediate Bad dephosphorylation, then allowing to form heterodimers with Bcl-X L to exert its apoptotic function (Gajewski and Thompson, 1996;Zha et al, 1996). In this sense, the role of serine phosphatases in the process of apoptosis has been also suggested (Morana et al, 1996). Alternatively, Tat may inhibit the activity of the kinase Raf-1, which has been shown to phosphorylate Bad inhibiting its pro-apoptotic function (Wang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Human ML-1 cells show chromatin condensation, DNA fragmentation and intracellular acidification within 4 h after a 30 min incubation with the topoisomerase II inhibitor etoposide (Morana et al, 1994(Morana et al, , 1996. This time period has been used for the studies reported here.…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular activity of this protease family can also be assessed by the cleavage of an endogenous protein, poly(ADP-ribose) polymerase (PARP) (Lazebnik et al, 1994). We have recently established a temporal order of events in apoptosis in which dephosphorylation of the retinoblastoma susceptibility protein Rb occurs upstream of cleavage of PARP, DNA digestion and apoptosis (Morana et al, 1996). In the current experiments, we show that zinc prevents all of these events, demonstrating that the protective action of zinc is upstream of both Rb dephosphorylation and activation of ICE/CED-3 proteases and not at the level of an endonuclease.…”
Section: Introductionmentioning
confidence: 99%
“…PP-1 promotes survival through regulation of p53 and other targets It has been well documented that inhibition of PP-1 or/and PP-2A by the marine algae toxins, okadaic acid and calyculin A, induces apoptosis of various types of cells (Boe et al, 1991;Ishida et al, 1992;Mellgren et al, 1993;Kiguchi et al, 1994;Weller et al, 1995;Fernandez-Sanchez et al, 1996;Morana et al, 1996;Sheikh et al, 1996;Yan et al, 1997;Li et al, 1998Li et al, , 2001aGarcia et al, 2003). However, why inhibition of PP-1 or/and PP-2A leads to apoptosis remains largely unknown.…”
Section: Dephosphorylation Of P53 Displays Strong Impact On Its Functmentioning
confidence: 99%